If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2secx + 7 = 3 Reorder the terms: 7 + 2cesx = 3 Solving 7 + 2cesx = 3 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 2cesx = 3 + -7 Combine like terms: 7 + -7 = 0 0 + 2cesx = 3 + -7 2cesx = 3 + -7 Combine like terms: 3 + -7 = -4 2cesx = -4 Divide each side by '2esx'. c = -2e-1s-1x-1 Simplifying c = -2e-1s-1x-1
| 5x+(x-4)=5x+x-10 | | 3x+18+6=9+7x+4x+3x | | 2(x+5)(x-2)=190 | | x^2-1+3x^2y-3xy=0 | | 4m^2-20am= | | 5x+12=7x+5 | | 22y-12(2y)+32=0 | | y=-(1/3y-13/3)+2 | | x^3-36x+72=0 | | 14a-21b+35= | | x=1/3(-x+2)-13/3 | | s-2w=0 | | 20x+50y+5z=500 | | 16a+8b+c=100 | | 8a^3-6a^2= | | 6y^2-36y+324=0 | | 14m^2n+7mn= | | (7n-1)(n+2)=0 | | 2y-12(2y)+32=0 | | 2s-3w=1 | | 2x^9-14x^7=0 | | (p+7)(p+2)=0 | | 3x-12=-x+4 | | 6p^2=-31p | | 2ln-9x=0 | | 8+ln-5n=7 | | 2+4x=55-41 | | 3(x+2)-2(x+1)= | | 50x^2+50x+50000000= | | 9000=92*1.8t | | w^2-12+3=0 | | 9(x+27)=4x-3 |